Vertebroplasty Increases the Incidence Of New Vertebral Compression Fractures Compared To Conservative Management - Maram Othman; Meshal Alshaalan; Abdulrahman Khawaji; Rawan Benkuddah; Hala Khalil; Khalid Alismail; Waleed Althobaity; Saleh Alreshoodi (The Arab Journal of Interventional Radiology)
Background Vertebral osteoporotic fractures are a major cause of morbidity and disability among the elderly population. This study sought to compare the incidence of new vertebral fractures in patients treated by vertebroplasty with that of those managed conservatively, while also assessing the potential risk factors contributing to the occurrence of these fractures. Materials and Methods The details of a total of 121 eligible subjects with radiologically proven osteoporotic vertebral fractures were retrieved from our archive between January 2010 and September 2019 and divided, based on the treatment method, into percutaneous vertebroplasty (PVP) (n = 60) and nonsurgical treatment (n = 61). The included subjects’ clinical data, demographic profiles, and imaging findings on plain radiography, CT, and MRI scans performed at baseline and within 24 months following treatment were reviewed and documented. Results The difference in the incidence of new fractures was statistically significant (p = 0.001), with rates of 70% (n = 32) in the vertebroplasty group and 30% (n = 14) in the conservatively treated cases reported at a median follow-up time point of approximately 4 months. The presence of liver disease (p = 0.037), a history of transplantation (p = 0.003), the use of steroids (p = 0.023), a low-bone mineral density (BMD) score (p = 0.023), and a higher number of fractures on baseline imaging (p = 0.013) were associated with a greater risk of subsequent vertebral fractures. Conclusions The incidence of acute fractures after PVP is higher than that among patients treated conservatively. Decision-making regarding the adoption of this intervention should take into consideration the risk factors leading to a greater risk of subsequent vertebral fractures, such as a higher number of fractures at baseline imaging, low-BMD score, patient comorbidities, and steroid use.